Gadamer and the transmission of history - Veith, Jerome, 1981- (Bloomington : Indiana University Press, 2015)
Observing that humans often deal with the past in problematic ways, Jerome Veith looks to philosopher Hans-Georg Gadamer and his hermeneutics to clarify these conceptions of history and to present ways to come to terms with them. Veith fully engages Truth and Method as well as Gadamer's entire work and relationships with other German philosophers, especially Kant, Hegel, and Heidegger in this endeavor. Veith considers questions about language, ethics, cosmopolitanism, patriotism, self-identity, and the status of the humanities in the academy in this very readable application of Gadamer's philo.
From structure to task -- Historical belonging as finite freedom -- The infinity of the dialogue -- New critical consciousness -- The bildung of community.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Gadamer, Hans-Georg, -- 1900-2002.; Gadamer, Hans-Georg, -- 1900-2002; PHILOSOPHY -- History & Surveys -- Modern; PHILOSOPHY -- Movements -- Phenomenology